Measurement of the WZ production cross section in pp collisions at [Formula: see text] and 8[Formula: see text] and search for anomalous triple gauge couplings at [Formula: see text] - Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Asilar, E; Bergauer, T; Brandstetter, J; Brondolin, E; Dragicevic, M; Erö, J; Flechl, M; Friedl, M; et al. (The European physical journal. C, Particles and fields, 2017)
The WZ production cross section is measured by the CMS experiment at the CERN LHC in proton-proton collision data samples corresponding to integrated luminosities of 4.9[Formula: see text] collected at [Formula: see text], and 19.6[Formula: see text] at [Formula: see text]. The measurements are performed using the fully-leptonic WZ decay modes with electrons and muons in the final state. The measured cross sections for [Formula: see text] are [Formula: see text] [Formula: see text] and [Formula: see text] [Formula: see text]. Differential cross sections with respect to the [Formula: see text] boson [Formula: see text], the leading jet [Formula: see text], and the number of jets are obtained using the [Formula: see text] data. The results are consistent with standard model predictions and constraints on anomalous triple gauge couplings are obtained.